Clinical orthopaedic rehabilitation : an evidence-based approach - Brotzman, S. Brent; Manske, Robert C.; Daugherty, Kay. (Philadelphia : Elsevier Mosby, 2011)
'In Clinical Orthopaedic Rehabilitation: An Evidence-Based Approach, Dr. S. Brent Brotzman and Robert C. Manske help you apply the most effective, evidence-based protocols for maximizing return to function following common sports injuries and post-surgical conditions. A well-respected, comprehensive source for evaluating, treating, and rehabilitating orthopaedic patients, the 3rd Edition guides you on the prevention of running injuries, the latest perturbation techniques, and the ACL rehabilitation procedures and functional tests you need to help get your patients back in the game or the office. You'll also find a brand-new spine rehabilitation section.'--pub. desc.
Hand and wrist injuries -- Elbow injuries -- Shoulder injuries -- Knee injuries -- Foot and ankle injuries -- The arthritic lower extremity -- Special topics -- Spinal disorders.
This book includes online access at www.expertconsult.com, please refer library staff for the password.
Keywords: Musculoskeletal System -- injuries; Orthopedics -- Methods; Evidence-Based Medicine -- methods; Musculoskeletal Diseases -- rehabilitation; Rehabilitation -- standards; Wounds and injuries -- Rehabilitation